Nonmicrobial Activation of TLRs Controls Intestinal Growth, Wound Repair, and Radioprotection - Stenson, William F.; Ciorba, Matthew A. (Frontiers in Immunology, 2021)
Abstract TLRs, key components of the innate immune system, recognize microbial molecules. However, TLRs also recognize some nonmicrobial molecules. In particular, TLR2 and TLR4 recognize hyaluronic acid (HA), a glycosaminoglycan in the extracellular matrix. The engagement of HA to these TLRs regulates host response in several important physiologic and pathophysiologic settings. In neonatal mice endogenous HA binding to TLR4 drives normal intestinal growth. HA binding to TLR4 in pericryptal macrophages results in cyclooxygenase2- dependent PGE2 production, which transactivates EGFR in LGR5+ crypt epithelial stem cells leading to increased proliferation. The expanded population of LGR5+ stem cells leads to crypt fission and lengthening of the intestine and colon. Blocking this pathway at any point (TLR4 activation, PGE2 production, EGFR transactivation) results in diminished intestinal and colonic growth. A similar pathway leads to epithelial proliferation in wound repair. The repair phase of dextran sodium sulfate colitis is marked by increased epithelial proliferation. In this model, TLR2 and TLR4 in pericryptal macrophages are activated by microbial products or by host hyaluronic acid, resulting in production of CXCL12, a chemokine. CXCL12 induces the migration of cyclooxygenase2-expressing mesenchymal stem cells from the lamina propria of the upper colonic crypts to a site adjacent to LGR5+ epithelial stem cells. PGE2 released by these mesenchymal stem cells transactivates EGFR in LGR5+ epithelial stem cells leading to increased proliferation. Several TLR2 and TLR4 agonists, including hyaluronic acid, are radioprotective in the intestine through the inhibition of radiation-induced apoptosis in LGR5+ epithelial stem cells. Administration of exogenous TLR2 or TLR4 agonists activates TLR2/TLR4 on pericryptal macrophages inducing CXCL12 production with migration of cyclooxygenase2-expressing mesenchymal stem cells from the lamina propria of the villi to a site adjacent to LGR5+ epithelial stem cells. PGE2 produced by these mesenchymal stem cells, blocks radiation-induced apoptosis in LGR5+ epithelial stem cells by an EGFR mediated pathway.